The Epigenetic Control of Hepatitis B Virus Modulates the Outcome of Infection - Koumbi, Lemonica; Karayiannis, Peter (Frontiers in Microbiology, 2016)
Epigenetic modifications are stable alterations in gene expression that do not involve mutations of the genetic sequence itself. It has become increasingly clear that epigenetic factors contribute to the outcome of chronic hepatitis B virus (HBV) infection by affecting cellular and virion gene expression, viral replication and the development of hepatocellular carcinoma. HBV persists in the nucleus of infected hepatocytes as a stable non-integrated covalently closed circular DNA (cccDNA) which functions as a minichromosome. There are two major forms of HBV epigenetic regulation: posttranslational modification of histone proteins associated with the cccDNA minichromosome and DNA methylation of viral and host genomes. This review explores how HBV can interphase with host epigenetic regulation in order to evade host defences and to promote its own survival and persistence. We focus on the effect of cccDNA bound-histone modifications and the methylation status of HBV DNA in regulating viral replication. Investigation of HBV epigenetic control has important clinical correlates with regards to the development of potential therapeutic regimens that will successfully eradicate HBV infection and deal with HBV reactivation in those undergoing treatment with demethylating agents.